Avaliação do uso dos conceitos de planejamento, controle e gestão de obras em empresas do setor da construção civil na região metropolitana de Curitiba - Wada, Karen Sayuri (2018)
With the evolution of the management forms and new challenges before the behavior of the society in search for more efficiency in the productive processes, the concern with more quality and productivity became fundamental. Through this stimulus, this work seeks to understand how the civil construction companies of Curitiba and metropolitan region have performed in relation to planning, management and control of civil work, focusing on the philosophy of lean construction. To reach this goal, the Survey method was used. This method allowed subdividing the questionnaire into 12 sections, with 105 variables. The sections have assisted in understanding since the client's considerations, supplier relations, until the closing procedures and sustainability. The answers followed the differential-semantic scale with seven points, where the minimum was the lack of activity and the maximum represented a highly developed practice. Fifty questionnaires were distributed, where for each group, those who did not obtain answers were eliminated. For the analysis, the data were grouped in Microsoft Excel and processed through the SPSS program - Statistical package for the Social Sciences. Through the analysis, it was possible to realize that the relationship between the companies and the client, suppliers of outsourced services, raw material suppliers, planning and management, budgets, civil work management, layout and construction site, post-closure are well developed, while control and follow-up have achieved developed results and sustainability and methods have achieved poor results.